2014
DOI: 10.1186/bcr3631
|View full text |Cite
|
Sign up to set email alerts
|

Malignant phyllodes tumors display mesenchymal stem cell features and aldehyde dehydrogenase/disialoganglioside identify their tumor stem cells

Abstract: IntroductionAlthough breast phyllodes tumors are rare, there is no effective therapy other than surgery. Little is known about their tumor biology. A malignant phyllodes tumor contains heterologous stromal elements, and can transform into rhabdomyosarcoma, liposarcoma and osteosarcoma. These versatile properties prompted us to explore their possible relationship to mesenchymal stem cells (MSCs) and to search for the presence of cancer stem cells (CSCs) in phyllodes tumors.MethodsParaffin sections of malignant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…In addition, these tumors appear to have significant intratumoral heterogeneity . Recent data have shown malignant PTs to display mesenchymal stem cell features with ability to be induced to or spontaneously undergo differentiation to other lineages . This correlates with previous reports of heterologous differentiation in PT, among which lipomatous differentiation appears most frequent .…”
Section: Discussionsupporting
confidence: 86%
“…In addition, these tumors appear to have significant intratumoral heterogeneity . Recent data have shown malignant PTs to display mesenchymal stem cell features with ability to be induced to or spontaneously undergo differentiation to other lineages . This correlates with previous reports of heterologous differentiation in PT, among which lipomatous differentiation appears most frequent .…”
Section: Discussionsupporting
confidence: 86%
“…Similar to metaplastic carcinomas, malignant PT showed enrichment for cancer stem cell-related biological processes. 50 In another study by Ang et al, 32 a heat map generated from 29 genes showed 3 distinct groups of benign, borderline, and malignant tumors, consistent with histologic classifications. The discrepancy in these studies is largely due to the smaller size of cohort studies with smaller numbers of borderline and malignant PT, and may also reflect differences in the criteria used for classifying PT.…”
Section: Molecular/genetic Featuresmentioning
confidence: 74%
“…Our laboratory and other investigators have recently found that EZH2 regulates breast cancer stem cells [10,13]. The aldehyde dehydrogenase I enzyme (ALDH1), a biomarker of normal and malignant human mammary stem cells [14,15], has been recently detected in association with mesenchymal stem cell markers in a group of malignant PTs [16]. However, the expression of EZH2 in PT has not been previously investigated, and the potential diagnostic and clinical significance of EZH2 and ALDH1 expression in a spectrum of benign, borderline, and malignant PTs is unknown.…”
Section: Introductionmentioning
confidence: 99%